Systemic Treatment of Adult Atopic Dermatitis: A Review - Megna, Matteo (Dermatol Ther (Heidelb), 2016)
Atopic dermatitis (AD) is a common chronic inflammatory skin disease that predominantly affects children. However, it can persist in adulthood and/or start at older ages. Due to its chronic nature and frequently occurring relapses, AD has a substantial effect on patients' quality of life, often requiring long-term systemic treatment, especially in adult patients, who are more frequently refractory to adequate topical treatment with mid- to high-potent corticosteroids and/or calcineurin inhibitors. Therefore, treatment with systemic therapies is often needed to take control of the disease, prevent exacerbations and improve quality of life. However, data regarding systemic treatment effectiveness and long-term safety in adult patients with AD are insufficient. Indeed, standardized international guidelines are lacking, and the treatment approach widely differs among diverse countries. This review focuses on the use of systemic treatments in adult AD patients analyzing published literature.